RANCANG BANGUN E-COMMERCE MENGGUNAKAN CMS OPENCART - Muhammad, Daniel; Tukino, Tukino (LPPM Universitas Putera Batam, 2021)
Batam Collection store is a bag and luggage store located in Baloi which is engaged in fashion. In processing, marketing sales of bags and luggage is using a simple way, that is only selling these products in housing, so there are obstacles in marketing process. Analyzing the old system of Batam Collection store, and then analyzing proposed new system and design an E-Commerce system using content manajemen system (CMS) is the point of the research. This research method uses the System Development Life Cycle process through the Water fall method. The results is to build an E-Commerce system that will facilitate sales activities and to get sales reports. In the E-Commerce system, the researcher will use OpenCart CMS for data processing. After the researcher built a product sales system with E-Commerce, the new system at the Batam Collection store could increase marketing and sales, as well as regulate product sales. The researcher hope that this new system can make the work easier for everyone involved.